Emaranhamento: caracterização, manipulação e consequências - Marcelo de Oliveira Terra Cunha (2005)
Entanglement is characterized, to the best knowledge of these days, from bipartite pure states to multipartite mixed states, and including the problems of di erent tensor product structures determination for a given quantum system and identical particles' entanglement. The manipulation of entanglement for impinging which way information on interferometers, as well as its later erasure (the so called \quantum erasure"), is presented, with emphasis on an experiment made by UFMG optics group and on a discussion about what is really quantum in such eraser. A quick introduction to the concepts of quantum state teleportation and quantum cryptography is given. Open quantum systems are put in perspective and, from this perspective, the environment e ects on an experiment made to explore the quantum-classical frontier are discussed. This analisys allows the proposal of modi cations for better exploring this frontier. The di erent time scales for dissipation, thermalization, and decoherence are obtained for the problem of one harmonic oscillator interacting with a huge set of other harmonic oscillators, in a situation which mimics the Schröodinger's cat. From the quantum information protection perspective, decoherence free subspaces and noiseless subsystems are discussed. Speci c models are studied and their experimental implementation discussed. An experiment realized to show the principles of decoherence free subspaces is also studied. In the considerações nais, the questions raised by these works are pointed.